PENGARUH TRUST DAN AFFECTIVE COMMITMENT TERHADAP FAMILY BUSINES CONTINUITY SUCCESSION PADA PERUSAHAAN KELUARGA DI FAMILY BUSINESS COMMUNITY UNIVERSITAS CIPUTRA SURABAYA - Gani, Sahril Sinuarta (PERFORMA, 2022)
In a family business, the issue of succession becomes important to keep the family company survive. There are two important things that play a role in family business succession, namely trust and affective commitment. This study aims to examine the effect of trust and affective commitment on family business continuity success. Research respondents were 87 college students of Ciputra Family Business, which were taken by purposive sampling method. The analysis used is multiple regression analysis. The results of the F test hypothesis indicate that the regression model used in the study is declared feasible. The results of the t-test analysis show that the variables of trust and affective commitment partially have a significant positive effect on family business continuity success for Cipoutra. It can be concluded that higher trust and affective commitment will increase the success of family business succession.